The Nutrition Knowledge, Food Label Literacy, and Snacking Habits as Determinants of Overweight Among Adolescents: A Case-Control StudyNutrition Knowledge, Food Label Literacy, and Snacking Habits as Determinants of Overweight Among Adolescents: A Case-Control Study - Lulu Luthfiya; Khonsa Habibatul Hayy; Kartika Pibriyanti; Hafidhotun Nabawiyah; Indahtul Mufidah (JURNAL KESMAS DAN GIZI (JKG), 2026)
Background: Overweight has become one of the most prevalent nutritional issues affecting adolescents in recent years. WHO says around 340 million teenagers in the world are overweight. In Indonesia, the prevalence of overweight is 9.5% and in East Java it is 11.3%. Overweight in women is higher than in men. Major factor of overweight was food intake which is influenced by eating pattern, which is a long-term impact of nutritional knowledge. Other factors that affect overweight are snacking habits and the abilty of nutritional information reading. This objectives to determine the relationship between nutritional knowledge, ability of label nutritional information reading and snacking habits with overweight in adolescents. Method: This research was observational analytical research with case control approach. The research was conducted in University based on  Islamic boarding school in East Java. The research sample in each group was 50 that was calculated by Lameshow formula. The sampling technique was purposive sampling. The independent variables were nutritional knowledge, ability of label nutritional information reading as measured using a questionnaire and snacking habits that was measured bt SQ FFQ. The dependent variable was overweight which measured by BMI/U for ages 17-18 years and BMI for ages >18 years. Data was analysed by chi square test Result: The relationship between nutritional knowledge with overweight has p-value> 0.05. The relationship between the ability of label nutritional information reading with incidence of overweight has a p-value <0.05. The relationship between snacking habits with incidence of overweight has a p-value <0.05. Conclusion: There was a relationship between the ability of label nutrition information reading and snack habits with overweight, but there was no relationship between knowledge and overweight. Suggestion: There is a need for a sustainable nutrition education program, including training on reading nutrition labels and controlling unhealthy snacking to prevent overweight among adolescents.